What reading strategies do competent esl students use? An investigation involving undergraduates from a Malaysian university - John Mark Storey; Loh Yoke Len; Chelster Sherralyn Jeoffery; Suyansah Swanto; Wardatul Akmam Din; Norazah Mohd Suki (Pusat Penataran Ilmu Bahasa, Universiti Malaysia Sabah, 2020)
The objective of this study was to establish the role played by reading strategies in the academic performance of university undergraduates. More specifically, the intention was to investigate the correlation between reading strategies, language knowledge and reading comprehension test performance among English as a Second language (ESL) learners at Universiti Malaysia Sabah (UMS). The instruments used in this mixed methods study were an English language knowledge test, a reading and test-taking strategy questionnaire, a multiple-choice reading comprehension test, and a structured interview involving a simulated recall session. Results analysed via SPSS indicated that two strategies in particular, Compensating for Missing knowledge (CMP) and Using Your Mental Processes (UYMP) strongly affected reading comprehension performance. Furthermore, these two strategies were the ones reported to be used most frequently by high attaining MUET students. In short, UMS undergraduates seem to employ specific cognitive strategies when engaging in English language reading assessments. It is hoped that the findings of this study will be useful in curriculum revision and will lead to the development of more effective reading courses for ESL learners in the future.